Action, Intention, and Reason - Audi, Robert (Ithaca, NY : Cornell University Press, 2019)
For the first time, Robert Audi presents in Action, Intention, and Reason a full version of his theory of the nature, explanation, freedom, and rationality of human action. Ove the years Audi has set out in journal articles different aspects of a unified theory of action. This volume offers the unity of a single, seamless book with thirteen self-contained chapters, two of them previously unpublished, and a new overview of action theory and the book's contribution to it. The book is divided into four parts, each addressing a major problem area. The chapters in Part One describe the motivational grounds of action, explicate desire, belief, intention, and volition, and give a distinctive account of their interconnections. In the second part, Audi sets out a theory of the explanation of action and argues that actions can be both law-governed and performed for reasons. The third part provides an account of free action and its relation to causation and responsibility. Chapters in the fourth and final part construct an account of rational action and its connections with practical reasoning, self-deception, and weakness of will.
Frontmatter -- Contents -- Preface -- Overview: Reason in Action -- PART I. DESIRE, INTENTION, AND VOLITION -- PART II. THE EXPLANATION OF ACTION -- PART III. FREEDOM, RESPONSIBILITY, AND THE CAUSATION OF ACTION -- PART IV. RATIONAL ACTION -- Index
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 25. Sep 2019).
JSTOR
Keywords: Act (Philosophy); Intentionality (Philosophy); Will; Free will and determinism; Responsibility; Reason; Volition; Personal Autonomy; Action (Philosophie); Intentionnalité (Philosophie); Volonté.; Libre arbitre et déterminisme.; Responsabilité.; Raison; reason; PHILOSOPHY / Epistemology; Act (Philosophy); Free will and determinism; Intentionality (Philosophy); Reason; Responsibility; Will